2022
DOI: 10.1186/s12877-022-03243-9
|View full text |Cite
|
Sign up to set email alerts
|

Staff-to-resident abuse in nursing homes: a scoping review

Abstract: Background Elder abuse in long-term care is an important public health concern with social, health-related, and economic implications. Staff-to-resident abuse is of particular interest since institutions should protect residents’ rights and prevent harm. To provide an up-to date comprehensive overview of staff-to-resident abuse in nursing homes, we performed a scoping review considering types of abuse, their prevalence and associated factors, descriptions, experiences, and preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…Studies (Feng et al, 2019; van der Cingel & Brouwer, 2021) have shown that there were still stereotypes about the nursing profession in society, that nursing work was simple and not professional, so that nurses were not respected and recognized as they should be. In addition, this study also found that due to the large workload and difficulty of long‐term care, coupled with their lack of ability, individual nurses were prone to vent their stress in an inappropriate form (Chen et al, 2020), which also exists in other countries (USA, Norway, UK, etc) (Hirt et al, 2022), seriously affects the quality of care and health of seniors. In this regard, nurses in long‐term care facilities should continuously strengthen their professional ethics, increase their humanistic care capabilities, and establish a respectable industry image.…”
Section: Discussionmentioning
confidence: 93%
“…Studies (Feng et al, 2019; van der Cingel & Brouwer, 2021) have shown that there were still stereotypes about the nursing profession in society, that nursing work was simple and not professional, so that nurses were not respected and recognized as they should be. In addition, this study also found that due to the large workload and difficulty of long‐term care, coupled with their lack of ability, individual nurses were prone to vent their stress in an inappropriate form (Chen et al, 2020), which also exists in other countries (USA, Norway, UK, etc) (Hirt et al, 2022), seriously affects the quality of care and health of seniors. In this regard, nurses in long‐term care facilities should continuously strengthen their professional ethics, increase their humanistic care capabilities, and establish a respectable industry image.…”
Section: Discussionmentioning
confidence: 93%
“…One critical but largely overlooked factor limiting the effectiveness of this safeguard is residents' fear of staff retaliation when voicing concerns about rights violations, poor care, and mistreatment. Specifically, in the context of the power imbalance between residents and staff (Hirt et al, 2022), the National Long-Term Care Ombudsman Resource Center (2018) asserted, "Fear of retaliation is one of the most common reasons residents do not want to pursue a complaint and disclose their identity. Since residents live in a facility and rely on staff for their basic needs, their fear of retaliation cannot be overemphasized.…”
mentioning
confidence: 99%
“…One critical but largely overlooked factor limiting the effectiveness of this safeguard is residents’ fear of staff retaliation when voicing concerns about rights violations, poor care, and mistreatment. Specifically, in the context of the power imbalance between residents and staff (Hirt et al, 2022), the National Long-Term Care Ombudsman Resource Center (2018) asserted, “Fear of retaliation is one of the most common reasons residents do not want to pursue a complaint and disclose their identity. Since residents live in a facility and rely on staff for their basic needs, their fear of retaliation cannot be overemphasized.”Fear of retaliation is defined as, “a concern or feeling of vulnerability that one’s actions may cause retaliation by another” (Connecticut Fear of Retaliation Workgroup) while retaliation is defined as, “acts of retaliation / revenge by facility staff in response to complaint to the facility, Ombudsman program, or state survey agency” (The National Ombudsman Reporting System).…”
mentioning
confidence: 99%
See 2 more Smart Citations